A Study of Appraisers’ Managerial Competencies towards the Intentions of Appraiser to Practice the Informal Performance Appraisal Process - Wong, Lee Wah (2009)
Selain daripada barangan dan modal, pekerja merupakan aset yang paling besar kepada sesuatu organisasi.